Gastro-oesophageal reflux disease in Asia - Goh, K.L.; Chang, C.S.; Fock, K.M.; Ke, M.; Park, H.J.; Lam, S.K. (Blackwell Publishing, 2000)
Gastro-oesophageal reflux disease (GORD) occurs more frequently in Europe and North America than in Asia but its prevalence is now increasing in many Asian countries. Many reasons have been given for the lower prevalence of GORD in Asia. Low dietary fat and genetically determined factors, such as body mass index and maximal acid output, may be important. Other dietary factors appear to be less relevant. Increased intake of carbonated drinks or aggravating medicines may influence the increasing rates of GORD in some Asian countries but no strong evidence links other factors, such as the age of the population, smoking or alcohol consumption, to GORD. The management of GORD in Asia is similar to that in Europe and North America but the lower incidence of severe oesophagitis in Asia may alter the approach slightly. Also, because Asians tend to develop stomach cancer at an earlier age, endoscopy is used routinely at an earlier stage of investigation. Gastro-oesophageal reflux disease is essentially a motility disorder, so short-term management of the disease can usually be achieved using prokinetic agents (or histamine (H2)-receptor antagonists). More severe and recurrent GORD may require proton pump inhibitors (PPI) or a combination of prokinetic agents and PPI. The choice of long-term treatment may be influenced by the relative costs of prokinetic agents and PPI.